Efektivitas Media Pembelajaran Augmented Reality Terintegrasi Aplikasi Unity Terhadap Kemampuan Berpikir Kritis Peserta Didik Geografi - Dermawan Dermawan; Erman Syarif; Ramli Umar; Hasriyanti Hasriyanti; Maddatuang Maddatuang (Jurnal Penelitian Pendidikan Geografi, 2025)
The critical thinking skills possessed by students today are very concerning. A student should have good analytical skills. Senior High School 5 Takalar is one of the schools that carries out remedial classes almost every semester. One of the basic competencies that is often remedied is the Lithosphere material. This research is a pre-experimental design with a Pre-test Post-test Control Group Design. The sampling process used a purposive sampling technique. 2 classes were obtained, namely class X.2 as the control class and X.1 as the experimental class using Augmented Reality media. The data analysis method was carried out by applying the paired t-test to test the hypothesis and the N-Gain test to assess the effectiveness of the learning media. The results of data analysis using the paired sample t-test for the experimental class with Augmented Reality obtained a Sig. (2-tailed) is 0.000 < 0.05, so it can be concluded that there is a significant influence on the differences in treatment in experimental classes that use Augmented Reality learning media or Ho is rejected and Ha is accepted. The results of the effectiveness analysis using the N-Gain test obtained a score of 0.7484, meaning that the level of effectiveness of the learning media applied in the experimental class was included in the high category.